2022
DOI: 10.1186/s12884-022-04656-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on the correlation between homocysteine-related dietary patterns and gestational diabetes mellitus:a reduced-rank regression analysis study

Abstract: Background This study aimed to evaluate the association between homocysteine-related dietary patterns and gestational diabetes mellitus. Methods A total of 488 pregnant women at 24–28 weeks of gestation between January 2019 and December 2020 were included. Demographic characteristics, dietary intake, and multivitamin supplement intake information were collected using a food frequency questionnaire (FFQ); fasting venous blood samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In the first trimester: AOR = 1.07, 95% CI = 1.02–1.12. Liu YH et al 2022 [ 38 ] China - Asia cases: 143 controls: 345 case-control no data available pregnancy dietary patterns Dietary pattern 2: OR = 2.96, 95% CI: 0.939–9.356, P = 0.004 Wang H et al 2021 [ 39 ] China - Asia n: 2099 cohort pregnant women were part of the participants in the Tongji Maternal and Child Health Cohort (TMCHC) study, 2013–2016. Gestational age between 8 and 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first trimester: AOR = 1.07, 95% CI = 1.02–1.12. Liu YH et al 2022 [ 38 ] China - Asia cases: 143 controls: 345 case-control no data available pregnancy dietary patterns Dietary pattern 2: OR = 2.96, 95% CI: 0.939–9.356, P = 0.004 Wang H et al 2021 [ 39 ] China - Asia n: 2099 cohort pregnant women were part of the participants in the Tongji Maternal and Child Health Cohort (TMCHC) study, 2013–2016. Gestational age between 8 and 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the lowest quartile, Q3 of the western pattern scores and Q3-Q4 of the traditional pattern scores were associated with a higher risk of GDM [ 24 ]. Another study conducted by Liu YH et al 2022 found relationship between homocysteine-related dietary patterns (positive factor loadings for wheaten food, livestock meat, eggs and negative factor loading for coarse cereals, green leafy vegetables, dried fungi and algae, milk group and nuts) and higher GDM risk (OR = 2.96, 95% CI: 0.939–9.356, P = 0.004) [ 38 ]. In the last two studies realised in Brazil, Nascimento GR et al 2016 did not find an association between dietary patterns during early pregnancy and GDM [ 59 ], but Sartorelli DS et al 2019 showed dietary pattern 1 (high rice, beans, and vegetables, with low full-fat dairy products, biscuits, and sweets) was inversely associated with GDM (OR 0.58; 95% CI 0.36–0.95; p = 0.03) [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 1713 documents were retrieved from Pubmed, Embase, The Cochrane Library, and Web of Science databases, from which 29 studies were selected by removing duplicates and filtering titles and abstracts. After reviewing the full-text articles, we selected 20 [ 16 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], including 12 cohort studies, five cross-sectional studies, and three case-control studies. Among the selected studies, eight of the 20 were conducted in China, three in the United Kingdom, two in Turkey, and one in Canada, Singapore, India, Spain, Australia, Italy, and Poland, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…An abnormal increase in Hcy is indicative of peripheral blood diseases. 16 Some studies have found that GDM can be accompanied by increased Hcy, that higher levels of Hcy in pregnant women correlate with the higher risk of developing diabetes after delivery. 17 Cys-C, is one of the commonly used indicators for clinical evaluation of renal function in patients, and can reflect changes in glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…This may cause rapid proliferation of smooth muscle cells and increase the risk of adverse pregnancy outcomes. 16 - 18 Cys-C is a type of low-molecular-weight non glycosylated protein that can reflect the extent of damage to glomerular filtration function and has certain predictive value for GDM and GDM-related complications. 18 , 20 …”
Section: Discussionmentioning
confidence: 99%